The parasite's long arm: a tapeworm parasite induces behavioural changes in uninfected group members of its social host - Beros, Sara (Proc Biol Sci, 2015)
Parasites can induce alterations in host phenotypes in order to enhance their own survival and transmission. Parasites of social insects might not only benefit from altering their individual hosts, but also from inducing changes in uninfected group members. Temnothorax nylanderi ant workers infected with the tapeworm Anomotaenia brevis are known to be chemically distinct from nest-mates and do not contribute to colony fitness, but are tolerated in their colonies and well cared for. Here, we investigated how tapeworm- infected workers affect colony aggression by manipulating their presence in ant colonies and analysing whether their absence or presence resulted in behavioural alterations in their nest-mates. We report a parasite-induced shift in colony aggression, shown by lower aggression of uninfected nest-mates from parasitized colonies towards conspecifics, potentially explaining the tolerance towards infected ants. We also demonstrate that tapeworm-infected workers showed a reduced flight response and higher survival, while their presence caused a decrease in survival of uninfected nest-mates. This anomalous behaviour of infected ants, coupled with their increased survival, could facilitate the parasites' transmission to its definitive hosts, woodpeckers. We conclude that parasites exploiting individuals that are part of a society not only induce phenotypic changes within their individual hosts, but in uninfected group members as well.